Odpowiedzi

Najlepsza Odpowiedź!
2010-01-02T17:16:25+01:00
1. x+2-3+y=0
x-2=5-2+y

x+y=0+3-2
x-y=5-2+2

x+y=1
x-y=5
_
x+y+x-y=1+5
2x=6/:2
x=3

2. 3x-3y+4x=8
3x-15y=5-9y

7x-3y=8
3x-15y+9y=5

7x-3y=8/*(-2)
3x-6y=5

-14x+6y=-16
3x-6y=5
_
-14x+6y+3x-6y=-11
-11x=-11/:(-11)
x=1

3. 6x-3+4y-8=9
10x-2+3=15x+5y+2

6x+4y=9+8+3
10x-15x-5y=2-3+2

6x+4y=20/*5
-5x-5y=1/*4

30x+20y=100
-20x-20y=4
_
30x+20y-20x-20y=104
10x=104/:10
x=10,4

4. 2x+2y-3x+6y=-7x-2
5x+5-6+2y=-4x-4y

2x+2y-3x+6y+7x=-2
5x+2y-4x-4y=6-5

6x+8y=-2
x-2y=1/*4

6x+8y=-2
4x-8y=4
_
6x+8y+4x-8y=2
10x=/:10
x=0,2

5. 4x+8-3y+3=x+y-3
3x-12-2y+4=4x-4y+4

4x-3y-x-y=-3-3-8
3x-2y-4x+4y=4-4+12

3x-4y=-14
-x+2y=12/*2

3x-4y=-14
-2x+4y=24
_
3x-4y-2x+4y=10
x=10



2010-01-02T17:21:29+01:00
1)x-1+y=0 x=5+y
5+y-1+y=0 x=5+y
4+2y=0 x=5+y
2y=-4 /:2 x=5+y
y=-2 x=5+y
y=-2 x=3

2) 3x-3y+4x=8 3x-15y=5-9y
7x-3y=8 3x-6y=5
-3y=8-7x/*(-1) 3x-6y=5
3y=7x-8 3x-6y=5
3y=7x-8 3x-2(7x-8)=5
3y=7x-8 3x-14x+16=5
3y=7x-8 -11x=-11/(-11)
3y=7x-8 x=1
3y=7*1-8 x=1
3y=-1/:3 x=1
y=1/3 x=1

3)3.
3(2x-1)+4(y-2)=9
2(5x-1)+3=5(3x+y)+2

6x-3+4y-8=9
10x-2+3=15x+y+2

6x+4y=20
10x+1=15x+y+2

6x+4y=20
-y=15x+2-10x-1

6x+4y=20
-y=5x+1/*(-1)

6x+4y=20
y=-5x-1

6x+4*(-5x-1)=20
y=-5x-1

6x-20x-4=20
y=-5x-1

-14x=24 /:(-14)
y=-5x-1

x=-24/14
y=-5x-1

x=-12/7
y=-5*(-12/7)-1

x=-12/7
y=60/7-1

x=-12/7
y=53/7

4.
2(x+y)-3(x-2y)=-7x-2
5(x+1)-2(3-y)=-4(x+y)

2x+2y-3x+6y=-7x-2
5x+5-6+2y=-4x-4y

6x-6y=-2
x+6y=1

6x+8y=-2
x=1-6y

6*(1-6y)+8y=-2
x=1-6y

6-36y+8y=-2
x=1-6y

6-28y=-2
x=1-6y

-28y=-8 /:(-28)
x=1-6y

y=8/28
x=1-6*8/28

y=2/7
x=-5/7

5.
4(x+2)-3(y-1)=x+y-3
3(x-4)-2(y-2)=4(x-y)+4

4x+8-3y+3=x+y-3
3x-12-2y+4=4x-4y=4

3x-4y=-8
-x-2y=12 /*(-1)

3x-4y=-8
x=2y-12

3*(2y-12)-4y=-8
x=2y-12

6y-36-4y=-8
x=2y-12

2y=28 /:2
x=2y-12

y=14
x=2*14-12

y=14
x=16